THE NATIONAL TECHNOLOGY INITIATIVE IN THE AGRICULTURAL AND FOOD SECTORS - Turker, Ufuk; Şahin, Kazım (Tuba-Turkish Acad Sciences, 2022)
Turkiye, with its geographical advantages and the products it produces in the field of agriculture, is making significant progress in the agricultural field day by day. The effects of technologies used in agriculture within the food, agriculture, energy chain and the increasing impact on related sectors and application areas have made the development of domestic and national technologies in many areas within the agriculture and food production chain even more strategic. The concept of national, on the other hand, refers to what belongs to a nation. The National Technology Initiative is of critical importance as the key to our country's ability to protect the data of its citizens and to develop and produce strategically valuable technology products with its own capabilities. The National Technology Initiative aims to contribute to the sectoral roadmaps, which are prepared in order to increase production efficiency, increase the efficiency of input use and reduce foreign dependency with alternative sources through energy efficiency, with technological product-based targets in sectors such as food, agriculture and livestock. Among these sectors, agriculture, like all economic sectors, uses a wide range of modern technologies. After the pandemic, agriculture has become much more technology and information intensive. Today, it requires much more than farming, that is, more integration and integration with other sectors, necessitating integration through digitalization. Realizing a national strategy to support national technologies is a process that takes into account the country's own rural development goals and includes all stakeholders in the industry. Turkiye's agriculture will reach the position it deserves in the global competitive environment brought by the digital age, in addition to current policies, this National Technology Initiative will be handled with the right strategy and policies that take into account the needs and expectations of all stakeholders. In this study, national technologies developed in our country in the field of agriculture are discussed and important information about their use and studies in this field are presented. It is expected that the national technologies developed in this context will increasingly continue to contribute and support the producers and farmers in the production and productivity of our country's agriculture in the future.
Keywords: National technology initiative; Technology; Agricultural technologies; Digital technologies; Innovation